Modulation of gonadotrophin induced steroidogenic enzymes in granulosa cells by d-chiroinositol. Issue 1 (December 2016) - Sacchi, Sandro; Marinaro, Federica; Tondelli, Debora; Lui, Jessica; Xella, Susanna; Marsella, Tiziana; Tagliasacchi, Daniela; Argento, Cindy; Tirelli, Alessandra; Giulini, Simone; La Marca, Antonio
Abstract Background d-chiroinositol (DCI) is a inositolphosphoglycan (IPG) involved in several cellular functions that control the glucose metabolism. DCI functions as second messenger in the insulin signaling pathway and it is considered an insulin sensitizer since deficiency in tissue availability of DCI were shown to cause insulin resistance (IR). Polycystic ovary syndrome (PCOS) is a pathological condition that is often accompanied with insulin resistance. DCI can positively affects several aspect of PCOS etiology decreasing the total and free testosterone, lowering blood pressure, improving the glucose metabolism and increasing the ovulation frequency. The purpose of this study was to evaluate the effects of DCI and insulin combined with gonadotrophins namely follicle-stimulating hormone (FSH) and luteinizing hormone (LH) on key steroidogenic enzymes genes regulation, cytochrome P450 family 19 subfamily A member 1 (CYP19A1 ) andcytochrome P450 side-chain cleavage (P450scc ) in primary cultures of human granulosa cells (hGCs). We also investigated whether DCI, being an insulin-sensitizer would be able to counteract the expected stimulator activity of insulin on human granulosa cells (hGCs). Methods The study was conducted on primary cultures of hGCs. Gene expression was evaluated by RT-qPCR method. Statistical analysis was performed applying studentt -test, as appropriate (P  < 0.05) set for statistical significance. Results DCI is able to reduce the gene expression ofCYP19A1, P450scc andinsulin-like growth factor 1 receptor (IGF-1R ) in dose–response manner. The presence of DCI impaired the increased expression of steroidogenic enzyme genes generated by the insulin treatment in gonadotrophin-stimulated hGCs. Conclusions Insulin acts as co-gonadotrophin increasing the expression of steroidogenic enzymes genes in gonadotrophin-stimulated granulosa cells. DCI is an insulin-sensitizer that counteracts this action by reducing the expression of the genesCYP19A1, P450scc andIGF-1R. The ability of DCI to modulate in vitro ovarian activity of insulin could in part explain its beneficial effect when used as treatment for conditions associated to insulin resistance.